2019
DOI: 10.3390/cells8091046
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of Plasma as a Key Factor in Assessment of Extracellular Vesicles by Light Scattering

Abstract: Extracellular vesicles (EVs) isolated from biological samples are a promising material for use in medicine and technology. However, the assessment methods that would yield repeatable concentrations, sizes and compositions of the harvested material are missing. A plausible model for the description of EV isolates has not been developed. Furthermore, the identity and genesis of EVs are still obscure and the relevant parameters have not yet been identified. The purpose of this work is to better understand the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 51 publications
(77 reference statements)
3
33
0
Order By: Relevance
“…that remain in suspension even after ENP isolation by differential ultracentrifug The Rh values of peak 2 were found in the range of 15-35 nm (diameter 30-70 nm those of peak 3 above 70 nm (diameter above 140 nm; see bold Rh values in Table tained with ηo ≈ 1.2 mPa s −1 ; the ones obtained with viscosity of water are repor Supplementary Materials). In agreement with literature reports [11,26,37,62], peaks 3 are attributed to ENPs, with peak 2 typically assigned to exosomes [11]. However The freezing and thawing of samples caused a decrease in the LS intensity and a simultaneous decrease in the peak heights for all samples.…”
Section: Analysis Of Ls Data At θ = 90°supporting
confidence: 91%
See 1 more Smart Citation
“…that remain in suspension even after ENP isolation by differential ultracentrifug The Rh values of peak 2 were found in the range of 15-35 nm (diameter 30-70 nm those of peak 3 above 70 nm (diameter above 140 nm; see bold Rh values in Table tained with ηo ≈ 1.2 mPa s −1 ; the ones obtained with viscosity of water are repor Supplementary Materials). In agreement with literature reports [11,26,37,62], peaks 3 are attributed to ENPs, with peak 2 typically assigned to exosomes [11]. However The freezing and thawing of samples caused a decrease in the LS intensity and a simultaneous decrease in the peak heights for all samples.…”
Section: Analysis Of Ls Data At θ = 90°supporting
confidence: 91%
“…On the other hand, additional filtering of samples before the LS measurement increased the contribution of 'peak 2' ENPs to I tot,90 • in both types of local fluids (compare PW*-C with PW*-C+F and PF*-C with PF*-C+F), presumably because strongly scattering larger species (e.g., aggregates) were removed from the suspension by filtration. Additionally, we observed that ultracentrifugation/filtration also led to a pronounced increase in R h values: R h,90 increased from 27 (15) nm for PW* (PF*) to 35 (26) nm for PW*-C (PF*-C) and 75 (86) nm for PW*-C+F (PF*-C+F), respectively, all for patient BP-E; c.f., Table S6). We conclude that the concentration of local fluids by ultracentrifugation may have a considerable effect on the particle size and size distribution, in particular in the case of low viscosity media, such as PW and PF.…”
Section: Angular Dependency and The Determination Of R G And ρmentioning
confidence: 84%
“…The particle sedimentation by centrifugal forces depends on the particle size, buoyant density, and viscosity of the solution. We reduced the sample’s viscosity by diluting plasma with PBS 54,55 , which improved the sedimentation efficiency. We pelleted and discarded cells, cell debris, apoptotic bodies, large microvesicles, and aggregates by a two-step conventional centrifugation at 4,500xg and then at 12,000xg 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Tluc activities were more highly retained in the EV fractions of differential ultracentrifugation samples, compared to ExoQuick samples. This finding suggests that the isolation methods could significantly contribute to the apparent phenotypes of isolated EVs (Bozic et al, 2019;Garcia-Romero et al, 2019;Brennan et al, 2020). Further characterization by immunoblot and single vesicle flow cytometry demonstrated that TSs were expressed on the surface of individual EVs.…”
Section: Discussionmentioning
confidence: 97%